P670 Identification of two additional susceptibility loci for Crohn's disease in Koreans. (27th May 2021) - Lee, H S; Jung, S; Ye, B D; Baek, J; Park, D; Park, S H; Yang, S K; Song, K
Abstract: Background: Genome-wide association studies (GWAS) have identified more than 240 susceptibility loci associated with IBD mainly in Caucasians, however, there are limited studies in other populations. Methods: To identify additional susceptibility loci in Asians, we expanded our previous study design (comprising a total of 1, 621 patients with Crohn's disease [CD] and 4, 419 controls), followed by replication in an additional 582 patients with CD and 845 controls. To determine biological processes associated with candidate genes for CD, we conducted pathway analyses by MAGMA using the results obtained through the current meta-analyses and the summary statistics of the largest meta-analysis in the European population as input. Results: The meta-analysis of Korean GWAS identified two novel susceptibility loci for CD at rs2240751 in the MFSD12 - C19orf71 - FZR1 - DOHH region on 19p13 ( p combined = 3.03 × 10 –8 ) and rs6936629 in the RFX6 - GPRC6A - FAM162B region on 6q22 ( p combined = 3.63 × 10 –8 ), of which rs6936629 showed significant association in European population ( p = 1.88 × 10 –4 ). Comparisons of the top 10 pathways for CD between the Korean and European data showed that MHC class Ⅱ protein complex, antigen binding, and response to antigenic stimulus-related pathways were more significant in the Korean population (Figure 1A), whereas cytokine and transcription factor-related pathways were more significant in the European population (Figure 1B). Conclusion: Our findings provide additional biological insight into CD pathogenesis and support the importance of studying IBD genetics in diverse populations.